Explaining Czech Inflation by a Time-Varying Taylor Rule - Pokorný, Tomáš; Maršál, Aleš; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2021)
In this thesis, we empirically and theoretically analyze the time-variability of the Czech National Bank’s Taylor rule policy parameters. Firstly, we estimate the time-varying policy parameters via Kalman filter in the state-space model for the period of 1995Q1-2020Q3. Secondly, we use the estimated parameters in a theoretical non-linear New Keynesian dynamic stochastic general equilibrium (DSGE) model of a small open economy to test the implications of time-variability of the policy parameters for the economy. The thesis contributes to understanding the dynamics of inflation resulting from an inconsistency of monetary policy parameters. We find that the weight on the inflation gap has gradually decreased in the last two decades. From the impulse-response analysis, we find that unanticipated shocks to the policy parameters harm the inflation stability and increase the business cycles fluctuations.
Vedoucí práce: Aleš Maršál
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: ekonomie [obor dipl. práce]; diplomové práce; master's theses